Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1115/1.4039782
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biogas Production in the Duckweed Anaerobic Digestion Process

Abstract: In order to enhance biogas production in the anaerobic digestion of duckweed, and duckweed with excess sludge as single and mixed substrates, the effects of hot alkali pretreatment and variation of the ratio of substrate to inoculum were investigated. The results showed that the delayed stage of anaerobic gas generation could be shortened when the two substrates were mixed during methane production, to give a cumulative gas yield of 2963 mL, which was 11% higher than the calculated value for the complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Now, at least two more rearrangements (in addition to the previously postulated one inversion and eight translocations) have to be assumed if the S. polyrhiza karyotype is more similar to that of the ancestor. Alternatively, eight (instead of six) translocations (involving ChrSi03, 04, 06, 07, 08, 11,12,16,18), and one fission (ChrSi09) 29 were required if the S. intermedia karyotype is the more ancestral one. Additionally, we found a positional change of the smaller 5S rDNA locus to ChrSi14 (instead of ChrSi07 which harbors sequences adjacent to the minor 5S rDNA locus on ChrSp06).…”
Section: Discussionmentioning
confidence: 99%
“…Now, at least two more rearrangements (in addition to the previously postulated one inversion and eight translocations) have to be assumed if the S. polyrhiza karyotype is more similar to that of the ancestor. Alternatively, eight (instead of six) translocations (involving ChrSi03, 04, 06, 07, 08, 11,12,16,18), and one fission (ChrSi09) 29 were required if the S. intermedia karyotype is the more ancestral one. Additionally, we found a positional change of the smaller 5S rDNA locus to ChrSi14 (instead of ChrSi07 which harbors sequences adjacent to the minor 5S rDNA locus on ChrSp06).…”
Section: Discussionmentioning
confidence: 99%
“…Lemnaceae (commonly known as water lens or duckweed) is a family of monocotyledonous water plants (Landolt, 1986;Landolt and Kandeler, 1987;Sree et al, 2016) characterized by the fastest growth rates among flowering plants (Sree et al, 2015b;Ziegler et al, 2015). As a consequence, the rate of biomass production is high, which provides the basis for different practical applications of duckweeds in the areas of food and feed sustainability (Landolt and Kandeler, 1987;Appenroth et al, 2017Appenroth et al, , 2018Sonta et al, 2019) and biotechnology (Zhao et al, 2015;Chen et al, 2018;Kaur et al, 2018;Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Ren et al (2018), the effects of hot alkali pretreatment and mixing ratio on AnCoD of duckweed and excess sludge were investigated. It was primarily indicated that through codigestion, the delayed stage of gas generation reduced and a 2963‐ml cumulative biogas was obtained.…”
Section: Hybrid Pretreatmentmentioning
confidence: 99%
“…The methane content of the produced gas was 57%, which was 13% and 9% higher than the methane achieved by single digestion of duckweed and excess sludge, correspondingly. Additionally, pretreatment of the duckweed in the mixture resulted in 8% further increase of the methane yield (Ren et al, 2018).…”
Section: Hybrid Pretreatmentmentioning
confidence: 99%